KEMASAN SEKUNDER THREE IN ONE TERHADAP MINAT BELI KONSUMEN PADA MADU SUMBAWA - Irwandi; Eka Putri, Yolli; Mikharatunnisa (Jurnal TAMBORA, 2020)
One of the resources found in the Sumbawa forest is honey. For the communitywho live around forest areas, honey is a source of incomefrom the forest as well as wild horse milk, coffee and candlenut beans which are a local mainstay.Communities around forest areas have the potential to accelerate developmentregions, however, are constrained by limited infrastructure, information and facilitieshuman resources, in addition to limited access to utilize forest resources.The majority of forest honey farmers in Sumbawa are still developing businesses andsell their products independently and use used bottles as packaginghoney. At first, packaging only functions as a container or wrapperserves to protect or cover, and to facilitate a product to be carried.Along with the times, packaging is required to be able to generate interestconsumers to buy. Based on these problems the authors doresearch on "Secondary Packaging Three In One Against Consumer Purchase IntentionOn Sumbawa Honey ". The method used in this research is a methodinterviews and distributing questionnaires using a Likert scale at 100respondents. The population in this study were customers of the second branch of PT Pos Indonesiawhich is located on Jl. Yos Sudarso No. 6A Sumbawa Besar. The author chooses the placebecause not only certain people who visit to send products and thingsthis can have an influence or good results on the research results forknow an overview of the research results from various characters and circlesPublic. The sampling technique used in this research is AccidentalSampling. Based on the research results, it was found that the visual packaging design(X1), packaging size (X2) and packaging quality (X4) have a significant effecton consumer purchase interest (Y), while product price (X3) has no effectsignificant on consumer purchase interest (Y).